1D and 2D modeling and simulation of radial combustion propagation on Fe 2O 3/Al thermite systems - Brito, Paulo (2014)
In previous works, a one-dimensional model was built to simulate the nonsteady radial combustion propagation on thin disk-shaped samples of Fe2O3/aluminum thermite mixtures and was successfully tested. Now, the purpose is to extend the referred model to the more sensible two-dimensional features of the samples, maintaining the main characteristics of the previous model: zero-order kinetics, conductive/radiative heat transfer, assumption of phase transitions, temperature and composition dependency for all system properties during propagation. Therefore, an adaptive numerical algorithm that conjugates a method of lines (MOL) strategy based on finite differences space discretizations, with a collocation scheme based on increasing level dyadic grids is applied for the solution of the problem. The particular integration method proves to cope satisfactorily with the steep traveling thermal wave in 1D and 2D spatial domains, either for trivial uniform mixing conditions, as in complex examples developed to feature more sophisticated circumstances, such as nonhomogeneous reactant mixing, which realistically replicate the observed experimental conditions.